Prediction of survival after neoadjuvant therapy in locally advanced rectal cancer – a retrospective analysis - Piringer, Gudrun; Ponholzer, Florian; Thaler, Josef; Bachleitner-Hofmann, Thomas; Rumpold, Holger; de Vries, Alexander; Weiss, Lukas; Greil, Richard; Gnant, Michael; Öfner, Dietmar (Frontiers in Oncology, 2024)
The aim of this retrospective analysis was to determine if the response to preoperative radio(chemo)therapy is predictive for survival among patients with locally advanced rectal cancer and may act as a potential surrogate endpoint for disease free survival and overall survival.Eight hundred seventy-eight patients from five centers were analyzed. There were 304 women and 574 men; the median age was 64.7 years. 77.6% and 22.4% of patients received neoadjuvant radiochemotherapy or short-course radiotherapy, resulting in a pathological complete response in 7.3%. T-downstaging and N-downstaging occurred in 50.5% and 37% of patients after neoadjuvant therapy. In patients with Tdownstaging, the 10-year DFS and 10-year OS were 64.8% and 66.8% compared to 37.1% and 45.9% in patients without T-downstaging. N-downstaging resulted in 10year DFS and 10-year OS in 56.2% and 62.5% compared to 47.3% and 52.3% without N-downstaging. Based on routinely evaluated clinical parameters, an absolute risk prediction calculator was generated for 5-year disease-free survival, and 5-year overall survival.T-downstaging and N-downstaging after neoadjuvant radiochemotherapy or shortcourse radiotherapy resulted in better DFS and OS compared to patients without response. Based on clinical parameters, 5-year DFS, and 5-year OS can be predicted using a prediction calculator.